2015
DOI: 10.1002/csr.1380
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gender Differences in the Impact of CSR Perceptions on Corporate Marketing Outcomes

Abstract: The purpose of this study was to investigate gender differences in corporate social responsibility (CSR) perceptions regarding business sustainability. Another important objective of this study was to explore the moderating role of gender on the relationship between CSR perception and three corporate marketing outcomes (i.e., corporate brand equity, corporate distrust, and corporate hypocrisy). Using a sample of 867 consumers in South Korea, a t-test and hierarchical moderated regression analysis were employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 82 publications
3
60
1
1
Order By: Relevance
“…Married people's recycling or sustainable product purchase behavior may be affected by their partners, or by social norms (Starr, ), while unmarried people may believe that companies have to be more supportive for communities as they may need more support from their communities. Finally, despite the previous research on the high tendency toward sustainable consumption behavior in female consumers and highly educated consumers (Carrigan & Attalla, ; Starr, ; Hur et al , ), the findings of this study showed that there are no differences between consumers' gender and educational levels in their views as to which activities are considered perfect or imperfect duties of corporations.…”
Section: Resultscontrasting
confidence: 99%
“…Married people's recycling or sustainable product purchase behavior may be affected by their partners, or by social norms (Starr, ), while unmarried people may believe that companies have to be more supportive for communities as they may need more support from their communities. Finally, despite the previous research on the high tendency toward sustainable consumption behavior in female consumers and highly educated consumers (Carrigan & Attalla, ; Starr, ; Hur et al , ), the findings of this study showed that there are no differences between consumers' gender and educational levels in their views as to which activities are considered perfect or imperfect duties of corporations.…”
Section: Resultscontrasting
confidence: 99%
“…Scholtens & Sievänen (2013) investigate the differences in the socially responsible investing (SRI) in Nordic countries and their study shows that Norway and Sweden, that have more femininity than Finland and Denmark, are both SRI pioneers. Hur et al (2016) and Jones et al (2017) find that female consumers have higher perceptions toward CSR than male consumers. Thanetsunthorn (2015) shows that masculinity has a significantly negative association with CSR performance on employee and community dimensions, but there is no significant relationship with the environmental dimension.…”
Section: Literature Review and Hypothesesmentioning
confidence: 98%
“…Contradicting views have been seen in existing studies pertaining to the impact of gender differences in CSR expectations and perceptions. Many past studies have shown that women place more priority on CSR issues and activities because they are more socially responsible than men (Alonso‐Almeida, Fernández de Navarrete & Rodriguez‐Pomeda, ; Hur, Kim, & Jang, ; Mejri & Bhatli, ). Brammer, Millington and Rayton () conducted an empirical study and found that women were highly interested in CSR, whereas men were more concerned with training provisions in organizations.…”
Section: Hypothesis Developmentmentioning
confidence: 99%